SMALL-SIDED GAMES SEBAGAI SARANA UNTUK MENGEMBANGKAN KEMAMPUAN PENGAMBILAN KEPUTUSAN DALAM PERMAINAN SEPAKBOLA - - Komarudin (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2013)
Small-sided soccer games are a form of exercise or activity by using football game field size smaller than the actualsize of a football field. With the hope of playing football hone skills both individually and team. In small-sided gamescan be inserted to the students in the form of the values of cooperation, problem-solving skills in the face of pressure,and the ability to make decisions quickly and appropriate so that team goals or groups can be achieved accordingto expectations this together. This writing tries to explain how noble values in the sport of soccer to teach childrenat an early age through the method of small-sided games. With hope we teach the importance of making the rightdecisions through fun games.Keywords: Small-Sided Games, Decision-Making, Soccer.